Spectral analysis of water level fluctuations in Belarusian and Polish lakes - Volchak, Aleksander; Choiński, Adam; Kirviel, Ivan; Parfomuk, Siergiej (Bulletin of Geography. Physical Geography Series, 2017)
Data regarding 25 lakes (9 Belarusian and 16 Polish lakes) provided the basis for spectral analysis of water level fluctuations. The obtained output data concerned a 55-year observation sequence covering years 1956-2010. The selection of lakes was determined by two factors, i.e. data continuity and inconsiderable anthropogenic impact. Depending on the course of the water level spectrum, the lakes were divided into three groups. The first group included the highest number of lakes (14) distinguished by smooth curves with no significant peaks (e.g. Lake Wygonoszczańskie). The second group shows four-year variability (e.g. Lake Łukomskie). The third group is distinguished by an even peak of three-year water fluctuation (e.g. Lake Łebsko). The location of the lakes categorised to those three groups suggests certain regionalisation. The first group is represented by the lakes of the central and northern part of Belarus, and eastern part of Poland. The second group includes lakes of the eastern part of Belarus, and the third group – lakes of central and north Poland. This suggests that next to local factors, the location of the distinguished groups of lakes may also be determined by regional factors.